Analysis of cold weather patterns over the period 1991-2012 - Farewell, Timothy S.; Hallett, Stephen H.; Truckell, Ian G. (Cranfield University, 2013)
Within the context of an observed increase in the numbers of burst pipes associated with colder winters in the Anglian water region, we have analysed temperature data for England and Wales from the period 1991-2012 to identify cold winter periods. To do so, we have calculated the annual accumulated temperature below 1 °C for each MORECS square over the winter period. The resulting data has been mapped for both the whole of England and Wales as well as just for the Anglian Water region. The data shows that the four winters between 2008-2012 were considerably colder than the preceding eleven winters. Additionally, for the winter of 2011-2012, the average temperature for all England of Wales was warmer than the 1991-2011 period average. However locally, in the Anglian Water region, the average temperatures were colder than the 1991-2011 average. The available MORECS data shows that while there are some periods of time with warmer winters (e.g. 1997-2008) and periods with colder winters (1990-1994, 1995-1997 and 2008- 2012), the lengths of these periods are considerably variable. From the MORECS data for the period 1991-2012, there does not appear to be a cyclical or predictable pattern in determining the harshness of the winter period.
Keywords: burst, soil, pipe, infrastructure, geohazard